Strategies to improve work discipline: Analysis of compensation, non-physical work environment, and training in a multibusiness companies in Gresik - Luluk Syarofaddina Eldianty; Ika Korika Swasti (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates the influence of compensation, non-physical work environment, and training on employee work discipline within a multi-business company located in Gresik. Grounded in human resource management and organisational behaviour perspectives, the study seeks to identify the key organisational factors that contribute to strengthening employee discipline in the workplace. A quantitative research design was employed using a purposive sampling technique involving 60 employees with fixed-term employment status. Primary data were collected through structured questionnaires and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings demonstrate that compensation exerts a positive and significant effect on employee work discipline, indicating that equitable and performance-oriented rewards contribute to higher levels of compliance and responsibility among employees. In addition, the non-physical work environment, including interpersonal relationships, communication climate, and organisational support, significantly enhances employee discipline. Training was also found to positively and significantly influence work discipline by improving employees’ competencies, awareness, and commitment to organisational standards. The study highlights the strategic importance of integrated human resource practices in fostering disciplined work behaviour and improving organisational effectiveness. These findings contribute to the broader literature on employee management and workplace performance, particularly within the context of developing economies and multi-sector business organisations. Keywords: Work Discipline; Compensation; Non-Physical Work Environment; Training